Protocol for the evaluation of a digital storytelling approach to address stigma and improve readiness to seek services among veterans. Issue 1 (December 2017) - Bunnell, Brian; Davidson, Tatiana; Hamblen, Jessica; Cook, Danna; Grubaugh, Anouk; Lozano, Brian; Tuerk, Peter; Ruggiero, Kenneth
Abstract Background Research suggests that at least 10% of veterans returning from Iraq and Afghanistan meet criteria for posttraumatic stress disorder (PTSD) related to their military experiences. National dissemination initiatives have increased veterans' access to best-practice interventions. However, treatment-seeking remains low among veterans with PTSD, often due to perceived stigma and other associated barriers. The National Center for PTSD recently developed and launchedAboutFace, a digital storytelling (DST) resource designed to help veterans recognize PTSD and motivate them to seek evidence-based treatment. The Ralph H. Johnson Veterans Affairs Medical Center (VAMC) and the National Center for PTSD have partnered to conduct pilot work to evaluate veterans' reactions toAboutFace to set the stage for a large-scale study to examine whetherAboutFace effectively reduces stigma and improves attitudes toward treatment-seeking among veterans. If effective, this DST approach may serve as a valuable national model for a variety of treatment-seeking populations. Methods During the first phase of the pilot, in-person usability assessments ofAboutFace will be conducted via semi-structured interviews with 20 veterans. Audio recordings of interviews will undergo transcription and coding. A report of the results of qualitative analyses of these interviews will be provided to the National Center for PTSD and will inform revisions to the site. In the second phase of the pilot, 60 veterans referred to a specialized PTSD clinic will be recruited to demonstrate and refine the methodology that we propose to use in a larger randomized controlled trial evaluation ofAboutFace . Veterans will be randomly assigned to receiveAboutFace plus standard education vs. standard education alone. Baseline and 2-week telephone assessments will be conducted with participating veterans to measure stigma, attitudes toward seeking mental health services, and treatment access/engagement. Discussion The feedback we receive in this pilot will be used to strengthen the quality of the DST website in preparation for a large-scale evaluation. Future work will involve evaluation of reach and impact of the site relative to stigma, attitudes toward seeking mental health service, and utilization of care. IfAboutFace is found to increase access to care, this finding would have broad and significant implications for overcoming barriers to care for veterans and other populations with stigmatized conditions. Trial registration Clinicaltrials.gov, NCT02486692